The Effects of High Protein Supplementary Feeding on the Growth of Stunting Children Aged 6-59 Months in Indonesia - Hendrini, Atika Rahmi; Pratiwi, Rina; Setyawati, Maria Mexitalia (International Journal of Child Health and Nutrition, 2026)
Background: Stunting remains a major public health problem in Indonesia, with a national prevalence of 21.6% in 2022 and nearly 30% in Semarang City. Inadequate protein intake is one of the key contributors, whereas animal-source protein supports growth, in part, through its effect on Insulin-like Growth Factor I (IGF-I). Objective: To evaluate the effect of high-protein supplementary feeding on the growth of stunted children aged 6-59 months using a quasi-experimental pretest-posttest design. Methods: A quasi-experimental pretest-posttest study was conducted involving stunted children aged 6-59 months who received supplementary food containing an energy-protein ratio of 10-18% for 90 days. Anthropometric outcomes included body weight (BW), height (Ht), weight-for-age Z-score (WAZ), height-for-age Z-score (HAZ), and weight-for-height Z-score (WHZ). Dietary intake, infection incidence, and compliance were also assessed. Paired t-test, Wilcoxon signed-rank test, and correlation analyses were applied as appropriate. Results: In the 101 study participants, energy (+128 kcal), protein (+6.77 g), fat (+11.8 g), and carbohydrate (+22.6 g) intake increased significantly (all p<0.001). Body weight (median Δ=0.50 kg; p<0.001), height (median Δ=1.90 cm; p<0.001), and WHZ (median Δ=0.06; p<0.001) improved significantly. WAZ increased by 0.17 (95% CI: −0.25 to −0.11; p<0.001), whereas HAZ showed no significant change (median Δ=0.05; p=0.608). Infection incidence was negatively associated with gains in body weight and height. Conclusion: High-protein supplementary feeding effectively improved nutrient intake and short-term growth indicators (BW, WAZ, WHZ), but did not significantly improve linear growth (HAZ), likely due to the short 90-day intervention period.